THE EFFECT OF CENTRAL BANK INDEPENDENCE LEVEL AND MACROECONOMIC FACTORS ON INFLATION IN INDONESIA, THAILAND, THE PHILIPPINES, MALAYSIA, AND VIETNAM 2004–2023 - Klara Lushanda Frelisia; Nurbetty Herlina Sitorus (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of the level of central bank independence, interest rates, Gross Domestic Product (GDP) growth, and exchange rates on inflation in Indonesia, Thailand, the Philippines, Malaysia, and Vietnam during the period 2004–2023. Secondary panel data were obtained from the World Bank–World Development Indicators and the Central Bank Independence Dataset developed by Garriga, then analyzed using panel data regression with the help of EViews software. Based on the results of the Chow Test and the Hausman Test, the Fixed Effect Model (FEM) was selected as the most appropriate estimation model, with Cross-section SUR (Panel Corrected Standard Errors/PCSE) correction to address heteroscedasticity issues. The results show that partially central bank independence has a positive but insignificant effect on inflation at the 5 percent significance level, so it is not able to explain inflation control in the sample countries. Interest rates have a negative and significant effect on inflation, indicating that interest rate increases are still effective in suppressing the inflation rate. GDP growth has a negative but insignificant effect on inflation, while the exchange rate has a positive and significant effect on inflation, so that exchange rate depreciation tends to increase inflationary pressures. Simultaneously, the four independent variables significantly influenced inflation, with a coefficient of determination (R²) of 0.780071. This finding indicates that inflation stability in the five ASEAN countries is more influenced by conventional macroeconomic factors, particularly exchange rates and interest rates, than by the level of central bank independence. The research findings are expected to provide input for monetary authorities and the government in formulating policies that support price stability by strengthening monetary policy coordination and managing exchange rate stability.